[PP.12.16] THE BLOOD PRESSURE TARGET, THE MACRO- AND MICRO-VASCULAR DAMAGE IN HYPERTENSIVES TREATED WITH INHIBITING RENIN-ANGIOTENSIN-SYSTEM AGENTS. (September 2017) - Nazzaro, P.; Schirosi, G.; De Benedittis, L.; Contini, M.; Moscatelli, F. Caradonna; Papagni, A.M.; Federico, F.
Abstract : Objective: Recent findings suggest that a lower therapeutic BP goals (<120/80 mmHg: HRBP) than those recommended by the actual guidelines (<140–135/85–90mmHg: GLBP) are associated to a more favorable cardiovascular prognosis. Aim of the study was to highlight the association between micro- and macro-vascular damage and BP values in adult hypertensives treated with ACEi or ARBs. Design and method: By medical visit (SBP/DBPoff), estimated history (HISThtn, months) and BP values at the diagnosis (HISTsbp/dbp), metabolic syndrome factors (nATPIII) and glomerular filtration rate (CKDepi), we studied 190 grade1–2 hypertensives, 55 HRBP, 92 GLBP and 43 with scarce BP control (SCBP) who underwent measurement of arterial stiffness (PWVcf), carotid intima-media thickness (IMT), preclinical indices, functional and structural, of arterial damage. Then, by videocapillaroscopy, the capillary density of the medial and distal phalanx of the 2nd, 3rd and 4th finger of the non-dominant hand at rest (CAP), venous congestion (CVC) and secondary capillary recruitment (REC), indices of structural and functional rarefaction, were determined. Results: ABPM confirmed the diagnosis. The study demonstrated similar metabolic characteristics but different vascular features (m ± s:d. * :p < .05, ** :p < .01, *** :p < .001 vs HRBP; ^ :p < .05, ^^ :p < .01, ^^^ :p < .001 vs GLBP) Figure. No caption available. Pearson analysis showed that the therapeutic SBP values are associated to the microvascular damage (CAP:−192 * ; CVC:−268 *** ; REC: −225 ** ). Conclusions: The findings suggest that a scarce BP control is associated to preclinical macro- and micro-vascular damage. The macrovascular subclinical damage is restrained by a satisfactorily BP control but a lower therapeutic target seems to restrain the microvascular rarefaction, often misrecognized. The findings, if confirmed in further proper studies, might explain, at least in part, the improved cardiovascular prognosis in hypertensives with a more aggressive BP target.